THE INFLUENCE OF THE LEADERSHIP STYLE OF THE HEAD OF THE MADRASAH AND MOTIVATION ON THE PERFORMANCE OF TEACHERS IN THE TSANAWIYAH MADRASAH FOUNDATION OF THE TAHFIDZUL QUR'AN ISLAMIC BOARDING SCHOOL MATHLAUL HUDA (MTS. YPPTQMH) AMBARAWA SUB-DISTRICT - Arya Duta; Epi Parela; Ahiruddin Ahiruddin (University of Sang Bumi Ruwa Jurai, 2023)
Teachers must have competencies that are in accordance with national learning standards in order to be able to carry out their duties and positions with good competency standards that create students to become knowledgeable humans and have certain skills. This study aims to examine the influence partially or simultaneously of variables of Leadership Style of the Head of Madrasah and Motivation on Teacher Performance in Madrasah Tsanawiyah Yayasan Pondok Pesantren Tahfidzul Qur'an Mathlaul Huda (MTs. YPPTQMH) Ambarawa District, Pringsewu Regency. This study took 35 respondents as a sample. The analytical tool used in this study is multiple linear regression. The tests carried out are with classical assumption tests, F tests, and t tests. The results of this study explain that: the leadership style of the head of the madrasah (X1) has a significant and positive effect on the performance of MTs. YPPTQMH Ambarawa teachers. The motivation variable (X2) has a significant and negative effect on the performance of MTs. YPPTQMH Ambarawa teachers. The leadership style variable of the head of the madrasah (X1) and the motivation variable (X2) have a significant effect together (simultaneously) on the performance of MTs teachers. YPPTQMH Ambarawa.